The International Division of Industries: Clustering and Comparative Advantage in a Multi-industry Model. - Venables, A (1999)
We consider a model with a large number of industries and agglomeration forces which cause each industry to concentrate in a single country. We show that the division of industries between countries is not unique, and that identical countries might have different numbers of industries and different wages and real incomes. Countries may gain by using policy to grab a higher proportion of world industry. Bounds on the set of equilibrium divisions of industry are found and we show how, with Ricardian differences in technology, there are equilibria with industries locating in the country where they have a comparative disadvantage.